Subpar reporting of pre‐analytical variables in RNA‐focused blood plasma studies - Céleste Van Der Schueren; Philippe Decruyenaere; Francisco Avila Cobos; Johanna Bult; Jill Deleu; Laudonia Lidia Dipalo; Hetty Hilde Helsmoortel; Eva Hulstaert; Annelien Morlion; Elena Ramos Varas; Kathleen Schoofs; Wim Trypsteen; et al. (Molecular Oncology, 2025)
Extracellular RNA (cell‐free RNA; exRNA) from blood‐derived liquid biopsies is an appealing, minimally invasive source of disease biomarkers. As pre‐analytical variables strongly influence exRNA measurements, their reporting is essential for meaningful interpretation and replication of results. The aim of this review was to chart to what extent pre‐analytical variables are documented, to pinpoint shortcomings and to improve future reporting. In total, 200 blood plasma exRNA studies published in 2018 or 2023 were reviewed for annotation of 22 variables associated with blood collection, plasma preparation, and RNA purification. Our results show that pre‐analytical variables are poorly documented, with only three out of 22 variables described in over half of the publications. The percentage of variables reported ranged from 4.6% to 54.6% (mean 24.84%) in 2023 and from 4.6% to 57.1% (mean 28.60%) in 2018. Recommendations and guidelines (i.e., BRISQ, ASCO‐CAP, BloodPAC, PPMPT, and CEN standards) have currently not resulted in improved reporting. In conclusion, our results highlight the lack of reporting pre‐analytical variables in exRNA studies and advocate for a consistent use of available standards, endorsed by funders and journals.